Analysis of Pulse Height Distributions of a Gas Electron Multiplier Detector by Using Cs-137 and Sr-90 Radioactive Sources - Ahn, Bong Jae; Hahn, Chang Hie (Journal of the Korean Physical Society, 2018)
A double-layer gas electron multiplier (GEM) chamber was developed at the Physics Department, Changwon National University. Its performance was evaluated using Cs-137 and Sr-90 radiation sources. Using a gas mixture filling of 85% argon and 15% carbon dioxide, in the one-channel GEM chamber (5 cm × 5 cm), the pulse height distributions were detected at atmospheric pressure and room temperature. The signals from the 32-keV and the 36-keV characteristic X-rays emitted owing to internal conversion in the Cs-137 source, as were signals from the beta emissions and 662-keV gamma rays. The signals due to the 662-keV gamma rays were separated from the other signals by placing 1 mm or 1.6 mm intercepting copper plates under the source. Furthermore, regions of the GEM detector in which the photo- and Compton electrons were produced by the X-rays (32 keV and 36 keV) and gamma rays (662 keV) were analyzed.